2009
DOI: 10.1007/s10552-009-9475-z
|View full text |Cite
|
Sign up to set email alerts
|

Association between cervical dysplasia and human papillomavirus in HIV seropositive women from Johannesburg South Africa

Abstract: ObjectiveTo examine the association between CD4 counts, HPV infection and the risk of cervical neoplasia among HIV-seropositive women.MethodsA cross-sectional observational study was conducted among 1,010 HIV-seropositive women using cytology-based Pap smears. HPV DNA testing using Linear Array genotyping assay (Roche) was carried out in a subset of 191 patients. Multivariable-adjusted prevalence ratios (mPR) and 95% confidence intervals (CIs) were estimated with log-binomial regression.ResultsAmong 1,010 HIV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
84
4
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(106 citation statements)
references
References 40 publications
15
84
4
3
Order By: Relevance
“…This data corroborate previous reports [46,47]. However, this rate is much lower than the rates reported in sub-Saharan Africa, which ranged from 49.8% to 73% [48] and India (27.5%) [15].…”
Section: Discussionsupporting
confidence: 90%
“…This data corroborate previous reports [46,47]. However, this rate is much lower than the rates reported in sub-Saharan Africa, which ranged from 49.8% to 73% [48] and India (27.5%) [15].…”
Section: Discussionsupporting
confidence: 90%
“…HAART increases the life expectancy of women living with HIV and AIDS and therefore not only allows for increased potential exposure time to HR-HPV but also permits for accumulation of cellular genetic changes that ultimately lead to cervical cancer [15]. While some studies have shown HAART to promote clearance of HR-HPV, its effect on the incidence and progression of high-grade cytological squamous intraepithelial lesions remains controversial [25]. The introduction of HAART more than 10 years ago in Zimbabwe has not been matched with a decline in the incidence of ICC [1,26].…”
Section: Discussionmentioning
confidence: 99%
“…In Ahdeich Grant et al [11,12], Hanskin's [13], Firnhasen [14], and Heard et al studies [15,16], they all said that low CD4 counts and increased HIV viral loads have an independent association with the incidence of delayed clearance of HPV infections as well as with the risk of progression of SIL (squamous intra-epithelial lesions).…”
Section: Cd4 Count and Its Association With The Colposcopic Findings mentioning
confidence: 99%